A high-resolution trajectory data driven method for real-time evaluation of traffic safety. (February 2022) - Hu, Yuping; Li, Ye; Huang, Helai; Lee, Jaeyoung; Yuan, Chen; Zou, Guoqing
Highlights: A method for real-time road safety evaluation based on traffic conflict was proposed. Effects of short-term traffic states on conflict risk were investigated and quantified. A high-precision evaluation model of traffic safety was developed by machine learning algorithms. Findings indicated the practicability of the proposed method for real-time safety evaluation. Abstract: Real-time safety evaluation is essential for developing proactive safety management strategy and improving the overall traffic safety. This paper proposes a method for real-time evaluation of road safety, in which traffic states and conflicts are combined to explore the internal relationship based on high-resolution trajectory data. In order to assess the real-time traffic safety at a lane level, the trajectory data of the HighD dataset from Germany are utilized to collect lane-based dataset. A surrogate safety measure, time-to-collision (TTC) index, is used for the conflict identification. A binary logistic regression model is employed to quantify the relationship between traffic states and conflicts. Moreover, machine learning methods, including support vector machine, decision tree, random forest, and gradient boosting decision tree, are applied for real-time evaluation. A total of 24 models are trained using the selected four classifier algorithms, and random forest achieves the best performance with 0.85 of the overall accuracy. The results show that the conflict risk can be well estimated by the proposed method. The findings of this study contribute to the high-precision evaluation of real-time traffic safety and the development of proactive safety management.